فعالية التخطيط الإستراتيجي وأثره على الأداء - مكي, حنان (My University, 2022)
Strategic planning has now become one of the most important tools that help achieve goals and objectives, Today, almost no global institution or organization is devoid of a special strategic plan, Which is keen to provide the requirements of its stability and growth as a basis for achieving its plans and achieving its goals, This requires that the organization work to improve its ability and efficiency in dealing with external changes and its opportunities, restrictions and threats, as well as working to raise its efficiency in dealing with its internal environment and its strengths and weaknesses, We find that each organization has a strategic plan at its level and is often derived from the organization's strategy to serve its performance. This is why our study came with the aim of analyzing this relationship between all these interactive variables within the organization, with a focus on the case of Mostaganem Port Corporation
دراسة حالة ميناء مستغانم